1999
DOI: 10.1159/000027668
|View full text |Cite
|
Sign up to set email alerts
|

A Rat T-Cell Line That Mediates Autoimmune Disease of the Inner Ear in the Lewis Rat

Abstract: In various patterns of sensorineural hearing loss including Ménière’s disease, which may show improvement in auditory function following immunosuppressive therapy, an isolated autoimmune disease of the inner ear has been postulated. Because of the lack of well-defined diagnostic criteria to identify autoimmune processes within the inner ear and the fact that the human inner ear is one of the few organs of the body not amenable to diagnostic biopsy, there has been great interest in developing animal models that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 19 publications
(27 reference statements)
0
9
0
Order By: Relevance
“…An immune injury in the ES has been suggested to play an important role in the pathogenesis of MD [Tomiyama et al, 1993[Tomiyama et al, , 1994[Tomiyama et al, , 1995. Recurrent inflammation of the ES leads to fluid homeostasis dysfunction of the inner ear and to conditions that resemble MD [Tomiyama, 1992;Gloddek et al, 1999].…”
Section: Introductionmentioning
confidence: 99%
“…An immune injury in the ES has been suggested to play an important role in the pathogenesis of MD [Tomiyama et al, 1993[Tomiyama et al, , 1994[Tomiyama et al, , 1995. Recurrent inflammation of the ES leads to fluid homeostasis dysfunction of the inner ear and to conditions that resemble MD [Tomiyama, 1992;Gloddek et al, 1999].…”
Section: Introductionmentioning
confidence: 99%
“…Several reports have shown that hearing loss and/or cochlear pathology occurs when guinea pigs are immunized with inner ear homogenate (7,(20)(21)(22). More recently, Gloddek et al (23,24) showed labyrinthitis but not hearing loss in naive Lewis rats adoptively transferred with activated T cells specific for inner ear homogenate. The predominant use of the guinea pig model with its limited availability of reagents and the exclusive use of crude antigen homogenate in prior studies preclude thorough immunologic characterization identification of target antigens and development of contemporary immunomodulatory treatment strategies.…”
Section: Discussionmentioning
confidence: 99%
“…PBMCs from ASNHL patients have been shown to elicit increased inhibition of leukocyte migration (17), increased proliferation (18), and have increased frequencies of IFN-γ-secreting T cells in response to human inner ear homogenate (19). The involvement of T cells in ASNHL is supported by animal studies showing cochlear pathology and/or hearing loss following immunization of guinea pigs with inner ear homogenate (7,(20)(21)(22) and following adoptive transfer of Lewis rats with T cell lines specific for inner ear homogenate (23,24). Most studies to date, however, have involved the use of bovine or human inner ear homogenate, thereby precluding characterization of the specific self-antigens as well as the autoreactive T cell repertoires involved in disease initiation and progression.…”
Section: Introductionmentioning
confidence: 99%
“…Immune activation may play a key role in the pathobiology of Cogan's syndrome. Experimental autoimmune keratitis and labyrinthitis have been induced in rat models, supporting aberrancy in the immune response as central to the pathobiology of Cogan's syndrome (Gloddek et al 1999;Verhagen et al 1999). The inflammatory nature of Cogan's syndrome is reflected in the lymphocytic and plasma cell infiltration seen in corneal tissue from patients with interstitial keratitis (Negroni and Tiberio 1969).…”
Section: Biologymentioning
confidence: 95%